The effect of giant magnetoresistance in Co/Cu/Co structure - Shkurdoda, Yu.A.; Dekhtyaruk, L.V.; Loboda, V.B. (Functional Materials, 2008)
The dependence of the giant magnetoresistance on the ratio of Co layers in as condensed Co/Cu/Co structures was studied both theoretically and experimentally. The maximum magnetoresistive ratio for this system was established to observe at equal thisknesses of the magnetic layers with 3 nm copper spacer.